Determining culprit lesion through the ECG pattern in wrapped LAD: A case series - Suryono, Suryono; Ardhianto, Pipin; Tohari, Achmad Ilham; Utama, Riawati; Hidayat, Muhammad Rijal Fahrudin; Amien, Muhammad Irsyad; Ramadhan, Hazbina Fauqi (Universitas Brawijaya, 2026)
Background: Wrapped left anterior descending (LAD) artery is defined as an LAD that supplies the apex and more than 25% of the inferior wall. Patients with wrapped LAD may have higher morbidity and mortality, and the culprit-lesion ECG pattern can differ from typical LAD occlusion, potentially leading to misinterpretation during primary percutaneous coronary intervention (PCI). Recognizing ECG patterns suggestive of wrapped LAD may help clinicians identify the culprit lesion and initiate appropriate therapy promptly.​ Case presentation: Four patients with ST-elevation myocardial infarction and angiographically confirmed wrapped LAD occlusion are presented, each demonstrating distinct culprit sites inferred from ECG patterns. The first was a 43-year-old Javanese man with mid-LAD occlusion; the second, a 40-year-old Javanese man with proximal LAD occlusion involving the first diagonal branch; the third, a 57-year-old Javanese man with isolated proximal LAD occlusion; and the fourth, a 59-year-old Javanese woman with mid wrapped LAD stenosis. All patients underwent successful primary PCI. Conclusion: Clinicians should consider wrapped LAD when ECG suggests combined anterior and inferior involvement, as the cardiac vector in wrapped LAD can produce patterns mimicking multivessel occlusion. In cases where the ECG appears to indicate two infarct territories, a single wrapped LAD occlusion rather than double-vessel disease should be suspected, which may refine culprit-lesion localization and procedural strategy during primary PCI.